Assessment of Science Laboratory Experiments (Physics, Chemistry, and Biology) in Inculcating Science Process Skills at the Higher Secondary Level - Tanwar, Pramila (SCHOOL SCIENCE, 2018)
The present research aimed to study the significance of science laboratory experiments in inculcating science process skills at the higher secondary level. Science laboratories play a very vital role in understanding the concept of science to students. Coordination of theory with practical is significant for corroborating concepts and stimulating interest in students' minds. Moreover, when the students handle the equipment themselves, it gives a more profound understanding. The researcher used the survey method for the collection of data. The research tools, i.e., science process skill tests for each physics, chemistry, and biology, were designed and implemented to understand the ground reality. Each process skill in Science (physics, chemistry, and biology) for a particular experiment is assessed by a five-point scale. The process skills are assessed as (i) Beginning stage, (ii) Foundation stage, (iii) Developing stage, (iv)Accomplished stage, and (v) Proficient stage. The scores given for the stages are 1,2,3,4 and 5, respectively. The mean of the process skill test in biology, physics, and chemistry was 11.18. The standard deviation of the scores was 4.459.